Chemotaxonomic Authentication of Herbal Drug Chamomile - AHMAD, MUSHTAQ; AJABKHAN, MIR; ZAFAR, MUHAMMAD; HASAN, AURANGZEB; SULTANA, SHAZIA; MUJTABA SHAH, GHULAM; BAKHSH TAREEN, RASOOL (Asian Journal of Chemistry, 2010)
The present study is based on the emerging concepts of authentication of problematic medicinal plants by using chemotaxonomic techniques. The major aim and objective of the study is to ascertain and solve the problems of adulteration and confusion of problematic herbal drugs used in traditional medicines. Unani herbal drug chamomile (Matricaria chamomilla) was authenticated by chemotaxonomic techniques from its adulterants i.e., Anthemis nobilis, Matricaria aurea and Inula vestita. Thin layer chromatography (TLC), scanning electron microscopy (SEM), light microscopy (LM), organoleptography, UV and IR analysis revealed the authentic source of chamomile is Matricaria chamomilla. It is concluded that when classical techniques combined with analytical techniques like SEM, TLC, UV and IR, then these may bring more appropriate results aimed as characterization and may assist the standardization of traditional herbal drugs available in market and utilized in industry.